Calcium Hydroxide Increases Human Umbilical Cord Mesenchymal Stem Cells Expressions of Apoptotic Protease-Activating Factor-1, Caspase-3 and Caspase-9 - Prasetyo EP; Kuntjoro M; Goenharto S; Juniarti DE; Cahyani F; Hendrijantini N; Nugraha AP; Hariyani N; Rantam FA (Dove Medical Press, 2021)
Eric Priyo Prasetyo,1,2 Mefina Kuntjoro,1,3 Setyabudi Goenharto,2 Devi Eka Juniarti,2 Febriastuti Cahyani,2 Nike Hendrijantini,3 Alexander Patera Nugraha,4 Ninuk Hariyani,5 Fedik Abdul Rantam6,7 1Doctoral Program, Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia; 2Department of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 3Department of Prosthodontics, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 4Department of Orthodontics, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 5Department of Dental Public Health, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 6Stem Cell Research and Development Center, Universitas Airlangga, Surabaya, Indonesia; 7Laboratory of Virology, Department of Microbiology and Immunology, Faculty of Veterinary Medicine, Universitas Airlangga, Surabaya, IndonesiaCorrespondence: Eric Priyo PrasetyoDepartment of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga, Jalan Mayjend Prof. Dr. Moestopo 47, Surabaya, IndonesiaTel/Fax +62 31 5030255Email eric-p-p@fkg.unair.ac.idPurpose: Calcium hydroxide is a gold standard dental material generally used for pulpal and periapical therapy including regenerative endodontic procedures because of its positive properties. However, evaluation about this material on stem cells is limited. Human umbilical cord mesenchymal stem cells (HUCMSCs) are potential to be used in regenerative therapy. Regenerative therapy needs a sustainable cell supply to maintain its regenerative capacity. The aim of this study was to ascertain the apoptosis result of calcium hydroxide on HUCMSCs through the expression of apoptotic protease-activating factor-1 (APAF-1), caspase-3, and caspase-9.Materials and Methods: This study used a thawed frozen stock of passage 5 HUCMSCs, grown in minimum essential medium (MEM) alpha containing calcium hydroxide at concentration of 0.1 microgram/mL for 1, 3 and 7 days. Polyclonal antibody with fluorescence isothiocyanate (FITC) label was used to evaluate the expressions. APAF-1, caspase-3, and caspase-9 expressions were recorded and compared on every observation day using fluorescence microscope. Analysis of variance was performed to analyze the significance among the results of treatment groups. The results were concluded significant if p< 0.05.Results: The addition of calcium hydroxide in MEM alpha medium increases HUCMSCs expression of APAF-1, caspase-3 and caspase-9 significantly, compared to the control group without calcium hydroxide (p< 0.05) in all the times. Day 1 showed the lowest increase followed by higher expressions on day 3 and day 7.Conclusion: HUCMSCs express increased APAF-1, caspase-3 and caspase-9 after in-vitro calcium hydroxide exposure. This should be considered when using calcium hydroxide on HUCMSCs for regenerative procedures with regard to other positive properties.Keywords: apoptosis, calcium hydroxide, caspases, mesenchymal stem cells, umbilical cord